To Visit and to Cut Down: Tourism, Forestry, and the Social Construction of Nature in Twentieth-Century Northeastern Ontario - Thorpe, Jocelyn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThis paper relies on the insights of social nature scholarship to trace the historical forest conservationist and tourism discourses through which Temagami, Ontario, became famous as a site of wild forest nature. The discursive practices associated with Temagami tourism and forest conservation in the early twentieth century did not merely reflect a self-evident wilderness, but rather constituted the region as a wild place for non-Native people both to visit and to extract for profit. The social construction of Temagami wilderness came to appear natural through the erasure of the Teme-Augama Anishnabai’s claim to the Temagami region, an erasure that persisted in environmentalists’ struggle to “save” the Temagami wilderness in the late 1980s. Revealing the histories and power relationships embedded in wilderness is part of the struggle toward greater justice.